2017
DOI: 10.3389/fimmu.2017.01806
|View full text |Cite
|
Sign up to set email alerts
|

Differential Susceptibility to Infectious Respiratory Diseases between Males and Females Linked to Sex-Specific Innate Immune Inflammatory Response

Abstract: It is widely acknowledged that males and females exhibit contrasting degrees of susceptibility to infectious and non-infectious inflammatory diseases. This is particularly observed in respiratory diseases where human males are more likely to be affected by infection-induced acute inflammations compared to females. The type and magnitude of the innate immune inflammatory response play a cardinal role in this sex bias. Animal models mimicking human respiratory diseases have been used to address the biological fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 62 publications
2
49
0
2
Order By: Relevance
“…23,25,31 Fetal-placental programming, genetic variation, and sex hormones can play a role in shaping the sex-specific innate and adaptive immune inflammatory responses. 23,24,30,[32][33][34][35] In support of this, a study analyzing serum from 331 hospitalized patients found that most female patients with severe COVID-19 had more than 100 AU/mL of SARS-CoV-2 IgG antibodies, while most male patients had less than 100 AU/mL. 36 Additionally, females generated a stronger IgG production early on in the disease course compared with male patients, which is consistent with preexisting literature.…”
Section: The Potential Role Of the X-chromosomesupporting
confidence: 78%
“…23,25,31 Fetal-placental programming, genetic variation, and sex hormones can play a role in shaping the sex-specific innate and adaptive immune inflammatory responses. 23,24,30,[32][33][34][35] In support of this, a study analyzing serum from 331 hospitalized patients found that most female patients with severe COVID-19 had more than 100 AU/mL of SARS-CoV-2 IgG antibodies, while most male patients had less than 100 AU/mL. 36 Additionally, females generated a stronger IgG production early on in the disease course compared with male patients, which is consistent with preexisting literature.…”
Section: The Potential Role Of the X-chromosomesupporting
confidence: 78%
“…Sex plays a role in innate, humoral, and cell-mediated immunity. It is well-established that adult males are more susceptible to infectious disease (1) and generate less reactive immune profiles (2,3), whereas adult females are more susceptible to inflammation and autoimmunity (4,5) but fare better when it comes to infectious disease (6). Females are reported to generate significantly higher levels of protective antibodies and cellmediated immunity following viral vaccinations against measles, rubella, rabies, smallpox, dengue, mumps, influenza, yellow fever, and hepatitis A and B (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Lung physiology, and specifically microbiota composition, affects the severity and progression of chronic respiratory disease states with observed gender differences [ 1 , 38 ]. The respiratory microbiome appears to have sex-specific signatures and is susceptible to a range of host immune and inflammatory consequences [ 39 , 40 ]. Continuous chronic inflammation is reported as more deleterious in females potentially contributing to greater tissue damage and their observed worse disease severity [ 41 ].…”
mentioning
confidence: 99%